2016
DOI: 10.1111/jwas.12305
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Identification of Vibrio natriegens from Diseased Portunus trituberculatus in China

Abstract: In July 2010, heavy mortalities were seen in cultured swimming crabs, Portunus trituberculatus, from Jiangsu Province in China. Two isolates, XA1 and XA2, were isolated from cardiac muscle and somatic muscle of the moribund crabs on ZoBell's marine 2216E agar and were confirmed as the causative agent for the mass mortalities seen on that farm. The morphological and physiological characteristics as well as the biochemical tests of the two isolates were identical and were similar to Vibrio natriegens. Both were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…is found distributed in salt march mud, estuarine habitats and also widespread in the ocean, andd has a faster growth rate compared with any known non‐pathogenic bacteria (Payne, 1958; Schleicher et al, 2018). However, there is a report on infection with this bacterium of a marine crustacean by Bi et al (2016), who found that V. natriegens strains can produce mortality of ≤85% in the cultured swimming crab, Portunus trituberculatus . Villaseñor et al (2015) identified V. natriegens in biofloc sample cultures, with the capacity to use different carbon and nitrogen sources with high efficiency, making it able to defeat pathogenic bacteria in the carbon and nutrient biofloc environment.…”
Section: Discussionmentioning
confidence: 99%
“…is found distributed in salt march mud, estuarine habitats and also widespread in the ocean, andd has a faster growth rate compared with any known non‐pathogenic bacteria (Payne, 1958; Schleicher et al, 2018). However, there is a report on infection with this bacterium of a marine crustacean by Bi et al (2016), who found that V. natriegens strains can produce mortality of ≤85% in the cultured swimming crab, Portunus trituberculatus . Villaseñor et al (2015) identified V. natriegens in biofloc sample cultures, with the capacity to use different carbon and nitrogen sources with high efficiency, making it able to defeat pathogenic bacteria in the carbon and nutrient biofloc environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been verified as a local, highly prevalent, pathogen and has been isolated from aquatic animals and the environment. The pathogenicity of V. natriegens to aquatic animals seems to have been underestimated (Bi et al, 2016;Deng et al, 2004;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A forward inner primer (FIP), a reverse inner primer (BIP), and two outer primers (F3 and B3) were chosen and synthesized by Sangon Biotech (Shanghai) Co., Ltd. Information relating to the primers is shown in Table 1 and Figure 1. In addition, 16S rDNA primer (27f/1942r) (Bi et al, 2016) and dulplex PCR primer (data not shown) were used to ascertain the specificity and sensitivity of LAMP assays. Optimization for LAMP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations